Vertebral compression fracture after stereotactic ablative radiotherapy in patients with oligometastatic bone lesions from hepatocellular carcinoma - Tae Hyung Kim; Jina Kim; Joongyo Lee; Taek-Keun Nam; Young Min Choi; Jinsil Seong (Clinical and Translational Radiation Oncology, 2023)
Background and purpose: Stereotactic ablative radiotherapy (SABR) is popularly used to treat bone metastasis. Despite its efficacy, adverse events, including vertebral compression fracture (VCF), are frequently observed. Here, we investigated VCF risk after SABR for oligometastatic vertebral bone metastasis from hepatocellular carcinoma. Materials and methods: A total of 84 patients with 144 metastatic bone lesions treated at three institutions between 2009 and 2019 were retrospectively reviewed. The primary endpoint was VCF development, either new or progression of a pre-existing VCF. VCFs were assessed using the spinal instability neoplastic score (SINS). Results: Among 144 spinal segments, 26 (18%) had pre-existing VCF and 90 (63%) had soft tissue extension. The median biologically effective dose (BED) was 76.8 Gy. VCF developed in 14 (12%) of 118 VCF-naïve patients and progressed in 20 of the 26 with pre-existing VCF. The median time to VCF development was 6 months (range, 1–12 months). The cumulative incidence of VCF at 12 months with SINS class I, II and III was 0%, 26% and 83%, respectively (p < 0.001). Significant factors for VCF development were pre-existing VCF, soft tissue extension, high BED, and SINS class in univariate analysis, and pre-existing VCF in multivariate analysis. Of the six components of SINS, pain, type of bone lesion, spine alignment, vertebral body collapse, and posterolateral involvement were identified as predictors of VCF development. Conclusion: SABR for oligometastatic vertebral bone lesions from HCC resulted in a substantial rate of new VCF development and pre-existing VCF progression. Pre-existing VCF was significant risk factor for VCF development, which require special attention in patient care. Patients with SINS class III should be considered surgical treatment rather than upfront SABR.